Professional Teeth Scaling by Dentists and Dental Therapists During COVID-19 Pandemic - Babatope Osagbemiro; Modupeoluwa Soroye (Khalij-Libya Journal of Dental and Medical Research, 2021)
The recent advent of the COVID-19 pandemic has caused widespread public health concerns and affected provision of health care including the delivery of professional teeth scaling by dental professionals. A cross-sectional online survey of dentists and dental therapists in Rivers State, Nigeria. Questionnaires were distributed to consenting participants using SurveyMonkey. Data were collected on sociodemographic, practice of scaling, and knowledge of recommended guidelines by WHO/CDC on the use of preoperative mouth rinses and Personal Protective Equipment (PPE). Data analysis was done and level of significance was set at p-value < 0.05. Sixty-three dentists and 34 dental therapists participated in this study with a mean age of 35.71±8.58 years. About two-third of the respondents did not perform teeth scaling for their patients during the early pandemic period. Fifty percent of dental professionals in government owned dental clinics performed teeth scaling while none of the private clinic staff did the procedure. The major reason for not performing the procedure was non provision of PPEs followed by fear of contacting the virus. Most (84.1%) of the dentists and 47.1% of dental therapists demonstrated a good knowledge of the recommended guidelines. Almost all (94.7%) of the private clinic staffs demonstrated a good knowledge compared to 65.4% of dental professionals in the government owned clinics. More than half of the dentists and only a few dental therapists performed scaling for their patients during the early period of the pandemic. Dentists and private clinic staffs demonstrated a good knowledge of the recommended guidelines for treatment.